The Implementation of the Independent Curriculum in Grade X Physics Learning at Senior High Schools - Masfufa Masfufa; M. Sidin Ali; Helmi Helmi (Postgraduate, University of Mataram, 2025)
This study aims to analyze the planning, implementation process, and assessment of the Independent Curriculum implementation in physics learning for Grade X students at public senior high schools (SMA Negeri) in Polewali Mandar Regency. This research employs a quantitative descriptive analysis method. The independent variable in this study is the implementation of the Independent Curriculum, while the dependent variable is physics learning. Data were collected through questionnaires distributed to 1,022 Grade X students in Polewali Mandar Regency, who served as the research subjects, as well as through interviews and direct observations with 10 Grade X physics teachers in the region, who also served as research subjects. The validity of the questionnaire instruments, interview guidelines, and observation guidelines was ensured through expert validation. The analysis results indicate that: overall, the planning of the Independent Curriculum implementation in physics learning has been carried out effectively; overall, the implementation of the Independent Curriculum in physics learning has been carried out effectively; and overall, the assessment implementation of the Independent Curriculum in physics learning has also been carried out effectively.